Analysis of the Health Assessment of Savings and Loan Cooperatives in Mataram City - Swari, Desak Nyoman Kumala Citra; Sasanti, Elin Erlina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study discusses the health assessment of savings and loan cooperatives in Mataram City. The health assessment of these cooperatives is evaluated based on governance, risk profile, financial performance, and capital, according to the Technical Guidelines of the Deputy for cooperatives No. 15 of 2021. This research employs a descriptive study with a quantitative approach, providing an objective description using numerical data to obtain information and answers from questionnaires. The subjects of this study are the Tri Dharma Kejari Mataram savings and loan cooperative (KSP Tri Dharma Kejari Mataram) and the Swastika savings and loan cooperative (KSP Swastika). The study reveals that the overall health score of KSP Swastika in 2023 is 79.65, indicating a